(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Tumors of the fourth ventricle in children pose a particular surgical challenge due to the proximity of eloquent neural parenchyma in the region. The two most common surgical routes to the fourth ventricle are the transvermian and telovelar approaches. Objectives: The goal of this study was to characterize the complications and morbidity related to the surgical management of pediatric fourth ventricle tumors Methods: this retrospective study includes 50 patients with 4th ventricle tumors from three centers (Dr.Saad Alwatry hospital, neurosurgical teaching hospital and Ghazi Al-Hriri hospital) in period from oct.2021 to oct.2022 . Preoperative imaging and clinical notes were reviewed to extract data on presenting symptoms, surgical techniques, and postoperative complications. Results: Across the whole series, the transvermian approach was more frequent than the telovelar approach (60% vs 40%). The most common postoperative deficit was cerebellar mutism syndrome (CMS12%), followed by new weakness (10%), cranial neuropathy (8%), and new gait abnormality/ataxia (6%). There was no significant difference in the rate of CMS between telovelar or transvermian approaches (p = 0.722). Conclusions: Surgical management of pediatric fourth ventricle tumors continue to evolve. CMS is enduringly the major postoperative complication in this patient Population.